2020
DOI: 10.3390/agronomy10010058
|View full text |Cite
|
Sign up to set email alerts
|

Biochar Integration with Legume Crops in Summer Gape Synergizes Nitrogen Use Efficiency and Enhance Maize Yield

Abstract: Besides carbon (C) sequestration, biochar (BC) is recently believed to deliver multiple eco-friendly benefits to the soil for enhancing crop productivity. Use of mineral fertilizers coupled with BC been suggested a promising sustainable strategy for increasing crops yield. However, imperative study is needed to investigate (1) BC integration with multiple legumes crop adjusted in summer gape for pooling more organic carbon and nitrogen, and (2) subsequently looking into its synergism with mineral N in the foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Significant interactions between biochar and N fertilizer on rice grain and straw yield were reported by MacCarthy et al [40] and, similarly, on rainfed rice yield and yield components by Oladele et al [41]. In two-year field experiments, biochar and N applications significantly increased grain yield and the above ground biomass of maize [42]. Nowadays, the combination of biochar with compost is also regarded as a promising approach to improve soil quality and crop growth.…”
Section: Introductionmentioning
confidence: 78%
“…Significant interactions between biochar and N fertilizer on rice grain and straw yield were reported by MacCarthy et al [40] and, similarly, on rainfed rice yield and yield components by Oladele et al [41]. In two-year field experiments, biochar and N applications significantly increased grain yield and the above ground biomass of maize [42]. Nowadays, the combination of biochar with compost is also regarded as a promising approach to improve soil quality and crop growth.…”
Section: Introductionmentioning
confidence: 78%
“…Therefore, one time use of biochar application for long term outputs in sustainable agriculture is economically feasible and can be adopted on a mass scale [ 13 ]. Previously it is documented that biochar combined with N fertilizer increases plant productivity [ 14 ], reduces greenhouse gas emissions [ 15 ], enhances soil physiochemical properties, and promotes the growth of beneficial soil biota [ 8 ]. Biochar is a soil conditioner that promotes soil microbial activity and improves grain quality [ 9 ], improves soil N accessibility and retention, decreases soil bulk density, improves the water-holding capacity of soil, increases the pH and cation exchange capacity, increases the abundance of beneficial microorganisms, and reduces the bioavailability of heavy metals, all of which improve plant photosynthesis [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gong et al [ 7 ] reported that sole biochar promoted SMEs, related genes expression and starch properties in pot experiment. Furthermore, our previous one season pot experiment results showed that biochar plus N fertilizer enhanced SMEs and starch content as compared to sole N applied treatment [ 14 ]. More research is needed under field condition to explore the ability of biochar application combined with inorganic fertilizer to promote the activity of SMEs, increase the expression of related genes, and increase the starch and amylose content of rice.…”
Section: Introductionmentioning
confidence: 99%
“…The term "sustainable agriculture" is defined as the consolidation of bioprocesses, chemical processes, physical activities, ecological processes, and socio-economic sciences in a holistic manner to design new agricultural practices that are safe and environmentally friendly [6]. Sustainable agriculture is a procedure by which agrofarming can nourish itself over an extended period by preserving and maintaining all its natural resources, e.g., maintaining the fertility of the soil, safeguarding surfaces and underground resources, developing renewable sources of energy, and seeking solutions to revamp farming methods to climate change [7,8]. Agrofarming must also consider the sustainability of the vast area and social groups.…”
Section: Introductionmentioning
confidence: 99%
“…Biochar is also being examined to rehabilitate environments, to diminish pollutant mobility in contaminated soils, and to reduce alteration of perilous elements to agronomic crops [7]. Mostly, biochar is produced from waste residues such as agricultural wastes, animal manures, and forest residues.…”
Section: Introductionmentioning
confidence: 99%